Liquidity and size effects on the Johannesburg Stock Exchange (JSE). Issue 3 (3rd July 2018) - McKane, Graeme; Britten, James
ABSTRACT: This study explores the existence of a liquidity premium on the Johannesburg Stock Exchange (JSE) and its potential interaction with the well-documented size effect. It builds on the stream of South African literature that examines liquidity as a standalone factor and adds further weight to its existence. Over the 2000-2015 sample period, this study finds evidence of a significant liquidity effect. Importantly, the liquidity premium is found to be separate from the size effect. Furthermore, the liquidity premium captures a different underlying effect than the value premium. The efficacy of Liu's (2006) Liquidity-Augmented Capital Asset Pricing Model (CAPM) as a useful asset-pricing model for the cross-section of returns on the JSE is examined and found to perform better than the Fama-French 3-Factor model.